Grievous Speech: Nathalie Stephens's Touch To Affliction and the City of Death - MacDonald, Tanis (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
Like all resonantly elegiac texts, Nathalie Stephens’s 2006 book Touch to Affliction does more than just locate or inscribe grief; it also challenges the historicized position of affect by dislocating the identity of the mourner, the City of Death through which the mourner roams, and the shifting identity of the mourner’s “lost beloved.” Stephens’s mourner politicizes the act of walking through the city: first, as a “dissonant body” that refuses gender norms, and second, as a stubborn physical presence of public mourning: that which is wrought by the nation, and that to which the nation can never fully respond. Alluding to philosophy about mid-twentieth-century violence, the narrator asks two resonant questions: “Where is the poet who will return language to the body?” and, more problematically, “Where is the body that is prepared to receive language?”